1998
DOI: 10.1128/jcm.36.11.3239-3242.1998
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Porphyromonas gingivalis and Periodontal Health Status

Abstract: Periodontitis is a common, progressive disease that eventually affects the majority of the population. The local destruction of periodontitis is believed to result from a bacterial infection of the gingival sulcus, and several clinical studies have provided evidence to implicate Porphyromonas gingivalis. If P. gingivalis is a periodontal pathogen, it would be expected to be present in most subjects with disease and rarely detected in subjects with good periodontal health. However, in most previous studies, P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
180
6
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(214 citation statements)
references
References 19 publications
14
180
6
5
Order By: Relevance
“…Our findings also confirm observations of Griffen et al (1998), who, using PCR technique, found an OR of 11.2 for P. gingivalis in adult patients with periodontitis. They found a healthy carrier rate for P. gingivalis of 25%, which is higher in comparison with the 9.9% found in our healthy group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings also confirm observations of Griffen et al (1998), who, using PCR technique, found an OR of 11.2 for P. gingivalis in adult patients with periodontitis. They found a healthy carrier rate for P. gingivalis of 25%, which is higher in comparison with the 9.9% found in our healthy group.…”
Section: Discussionsupporting
confidence: 92%
“…They found a healthy carrier rate for P. gingivalis of 25%, which is higher in comparison with the 9.9% found in our healthy group. This may be explained by the more strict clinical criteria we used for selection of periodontally healthy subjects in comparison with Griffen et al (1998), where they accepted CAL measurements up to 5 mm and they also used more samples than we did.…”
Section: Discussionmentioning
confidence: 97%
“…Porphyromonas gingivalis is a nonmotile asaccharolytic Gram-negative obligate anaerobe that requires heme (iron and protoporphyrin IX) for growth. It is recognized as a major pathogen of severe adult periodontitis (Griffen et al, 1998) and implicated in systemic inflammatory conditions including cardiovascular disease (Desvarieux et al, 2005;Rosenfeld & Campbell, 2011;Belstrom et al, 2012), rheumatoid arthritis (Hitchon et al, 2010;Routsias et al, 2011), preeclampsia (Barak et al, 2007;Lachat et al, 2011), and preterm delivery (Lachat et al, 2011). Porphyromonas gingivalis is able to invade multiple cell types, including human vascular and oral cell lines (Lamont et al, 1995;Deshpande et al, 1999;Progulske-Fox et al, 1999;Dorn et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The subgingival microflora in deepened periodontal pockets is dominated by Gram-negative anaerobic rods and spirochetes [1,3,5]. Actinobacillus actinomycetemcomitans [6], Porphyromonas gingivalis [7][8][9], Tannerella forsythensis [10,11], Prevotella intermedia [12,13] and Peptostreptococcus micros [14][15][16] are strong markers of periodontitis in adults and these species have been linked to progression of the disease. Fusobacterium spp.…”
Section: Introductionmentioning
confidence: 99%